Identification and monitoring of somatic mutations in circulating cell-free tumor DNA in lung cancer patients. (August 2019) - Francaviglia, Ilaria; Magliacane, Gilda; Lazzari, Chiara; Grassini, Greta; Brunetto, Emanuela; Dal Cin, Elena; Girlando, Salvatore; Medicina, Daniela; Smart, Chanel Elisha; Bulotta, Alessandra; Gregorc, Vanesa; Pecciarini, Lorenza; et al.
Highlights: Molecular characterization of lung cancer patients by ctDNA analysis. Successful use of ctDNA for mutation detection by both standard technologies and NGS. ctDNA NGS-genotyping by an in-house clinical molecular diagnostic workflow. ctDNA provides biomarkers for therapy selection and drug resistance monitoring. Abstract: Objectives: Circulating cell-free tumor DNA (ctDNA) isolated from the peripheral blood of non-small-cell lung cancer (NSCLC) patients provides biomarkers for both therapeutic target selection, particularly when direct tumor biopsy is unfeasible, and also for drug resistance monitoring. This study evaluates the reliability and feasibility of ctDNA analysis in an in-house clinical molecular diagnostic workflow. Materials and methods: Mutation profiling by both standard methods and Next-Generation sequencing (NGS) was carried out and compared on 2 independent lung cancer patient cohorts. Cohort 1 consisted of 50 EGFR -mutated NSCLC patients, established on tumour biopsy, for whom ctDNA was collected at disease progression after TKI-inhibitor treatment and could be used to monitor drug resistance. Cohort 2 consisted of 50 newly diagnosed lung cancer patients for whom tumour biopsy was not possible and only ctDNA was available, providing the possibility of biomarker identification. Results: ctDNA analysis of Cohort 1 verified the persistence of the tumour-detected EGFR activating mutation at disease progression by both standard and NGS methods, in 84% and 92% of the cases respectively. The T790M EGFR resistance mutation was identified in 71% of the ctDNA EGFR mutated samples providing vital information for their disease management. In newly diagnosed Cohort 2 patients, EGFR activating mutations were detected in 16% of the patients by both standard and NGS analysis of ctDNA in peripheral blood, providing indication to targeted-therapy otherwise unavailable for this group of patients. Conclusion: The presented study investigated lung cancer ctDNA analysis, comparing conventional methods versus NGS sequencing, and demonstrated the successful use of plasma ctDNA as a template for targeted NGS tumor gene panel in an in-house routine clinical practice. More importantly, these data underline the advantages of the clinical application of ctDNA NGS analysis for identification of therapeutic targets, real-time monitoring of therapy, and resistance mechanisms in lung cancer patients.